A prospective injury surveillance study in canyoning. Issue 4 (April 2018) - Ernstbrunner, Lukas; Schulz, Eva; Ernstbrunner, Matthaeus; Hoffelner, Thomas; Freude, Thomas; Resch, Herbert; Haas, Maximilian
Abstract: Introduction: Little is known about injuries in canyoning. It was the purpose of this study to determine injury rates, patterns, causes and risk factors in canyoning; and to identify targets for future injury prevention strategies. Methods: From May to October 2015, 109 participants from 17 different countries were prospectively followed via a monthly e-mail-based questionnaire. Results: During 13, 690 h of canyoning, 57 injury-events occurred. The overall injury-rate was 4.2 injuries/1000 h of canyoning. The hand (23%) and lower leg and foot (25%) were most frequently involved. Most of the injuries were mild (n = 27, 49%) and limited to the soft-tissue. There were seven severe injuries (12%) with two lateral malleolar fractures, both necessitating surgery. The majority of injuries were due to material failure (44%) and significantly more injury-events were reported when the tour included rappelling (p = 0.037). Canyoning guides suffered from significantly less injuries compared to beginners and advanced canyoneers (p < 0.001). Conclusions: The majority of canyoning injuries are mild. On the other side, roughly one-tenth suffered from severe injury. Canyoning guides are less prone to injury-events and beginners should consider performing tours with experienced guides. Notwithstanding, rappelling was the most common activity associated with an injury and the material used was deemed causative for an injury-event in almost half of all cases. Further improvement in canyoning equipment, frequent equipment service, and instructional courses to ensure adequate employment of equipment might minimize the risk of getting injured.